The histopathology and immunohistochemical expression of cell cycle regulators and mismatch repair gene proteins in colorectal carcinoma : a comparative study - Sookhayi, Raveendra (Division of Anatomical Pathology, 2015)
Introduction: It has been reported that HNPCC colorectal carcinomas demonstrate a better prognosis compared to sporadic carcinoma, however the exact mechanism for this is still uncertain. It is possible that tumour morphology, location and cell cycle markers may be indicators of the underlying molecular mechanism. In a resource limited setting these factors may help to stratify which cases need further molecular testing and genetic counselling. Aims and objectives: To characterise the macroscopic and microscopic pathology in three cohorts of patients. The cohorts include (1) patients with CRCs that are < 50 years and mutation negative, (2) < 50 years and DNA mismatch repair gene mutation positive and (3) more than 50 years (sporadic). To investigate the immunoexpression of the cell cycle regulators (p21, p27, p53, c-myc, cyclin D1 and cyclin E) and MMP-7 in each cohort. To compare the immunoexpression of each marker between cohort s. To correlate the immunoexpression of each marker with tumour type, stage and grade. Materials and methods: In total, 17 mutation negative, 15 mutation positive and 28 sporadic adenocarcinoma resection cases were available for study. The histopathological features of all cases were reviewed. The cases were stained with antibodies against p21, p27, cyclin D1, cyclin E, p53, c- myc MMP -7, MLH1, MSH2 and MSH6. Results were considered statistically significant if P < 0.05, and P <0.017 if 3 pairs of medians were compared. Results: The mutation positive tumours were more frequently right sided tumours and showed mucinous differentiation, tumour infiltrating lymphocytes and an expanding border. The sporadic and mutation negative cohort s showed similar morphology. In the sporadic cohort, the five tumours that were MLH1 negative demonstrated morphological features of MSI-H tumours. MLH1 mutations were the commonest. MLH1 immuno expression was lost in the mutation positive tumours and was statistically significant when compared to the other two cohorts. There was no statistical significance among the three cohorts for MSH2 and MSH6 immunoexpression. There was no statistically significant difference in immunoexpression for p21, p27, p53 and MMP-7 among the three cohorts. Furthermore, there was no association with tumour type and stage. Cyclin D1 expression was increased in the mutation positive cohort and was statistically significant when compared to the mutation negative cohort only. Cyclin E expression was also increased in the mutation positive cohort and was statistically significant when compared to the sporadic cohort only. Conclusion: The morphological features of colorectal carcinomas can be helpful in identifying MS I-H tumours and cases requiring further molecular studies. The cell cycle marker expression s did not explain the expected differences in patient outcome and prognosis. The mutation negative cohort in our population continues to remain enigmatic and further testing at the molecular level is required, that may reveal another novel pathway of colorectal carcinogenesis or other novel mutations in mismatch repair genes.